Rancang Bangun Alat Pendeteksi Warna Pakaian dengan Output Suara Berbasis Arduino Nano untuk Kemampuan Bina Diri Tunanetra - Arifah, Siti; Jaya, Putra (Lembaga Yasin AlSys, 2025)
This research aims to design and build a clothing color detection tool with Arduino Nano-based sound output to improve the self-help skills of blind people. The method used is the waterfall model, including the stages of needs analysis, design, implementation, and testing. This tool combines TCS3200 color sensor as input, Atmega328 microcontroller as processing unit, as well as DF Player and Micro SD for sound data processing which is finally displayed through the speaker. In its implementation, the program is made using Arduino IDE to control the color reading and sound output. The test results show that the device is able to accurately detect the color of clothing with a 100% success rate on 10 repeated trials. Tests were carried out on all subsystems, including color sensor input, microcontroller controller, DF Player plant, and speaker output. The resulting tool is portable, flexible, and allows blind people to choose clothes based on color without the help of a third party. Thus, this tool has the potential to support independence in self-help activities and improve the quality of life of users.